Bibliometric mapping of mesenchymal stem cell therapy for bone regeneration from 2013 to 2023 - Chen, Qianqian; Su, Yiqi; Yang, Zhen; Lin, Qiyuan; Ke, Yan; Xing, Dan; Li, Hui (Frontiers in Medicine, 2025)
Mesenchymal stem cells (MSCs) have shown significant potential in bone regeneration and regenerative medicine in recent years. With the advancement of tissue engineering, MSCs have been increasingly applied in bone repair and regeneration, and their clinical application potential has grown through interdisciplinary approaches involving biomaterials and genetic engineering. However, there is a lack of systematic reviews summarizing their applications in bone regeneration. To address this gap, we analyzed the latest research on MSCs for bone regeneration published from 2013 to 2023. Using the Web of Science Core Collection, we conducted a literature search in December 2024 and employed bibliometric tools like CiteSpace and VOSviewer for a comprehensive analysis of the key research trends. Our findings focus on the development of cell engineering, highlighting the advantages, limitations, and future prospects of MSC applications in bone regeneration. These insights aim to enhance understanding of MSC-based bone regeneration, inspire new research directions, and facilitate the clinical translation of MSC research.